History of Women in ihe Lohara Dynasty (London Journal of Research In Humanities and Social Sciences, 2023)
This paper explores the condition of upper class and lower class women in the Lohara Dynasty. In contrast to the condition of the women in other North Indian dynasties, women of the Lohara Dynasty participated with women in the state Rajatarangini by Kalhana portrays active participation of women in the state administration.